Effect of antiretroviral therapy on longitudinal lung function trends in older children and adolescents with HIV-infection - Rylance, Sarah (PLoS One, 2019)
INTRODUCTION: Chronic respiratory disease is a common cause of morbidity in children with HIV infection. We investigated longitudinal lung function trends among HIV-infected children, to describe the evolution of lung disease and assess the effect of anti-retroviral therapy (ART). METHODS: Prospective follow-up of two cohorts of HIV-infected children, aged 6 to 16 years, in Harare, Zimbabwe; one group were ART-naïve at enrolment, the other established on ART for a median of 4.7-years. Standardised spirometric assessments were repeated over a 2-year follow-up period. Forced expiratory volume (FEV(1)) and forced vital capacity (FVC) were expressed as Global Lung Initiative defined z-scores (FEV(1)z and FVCz). Linear mixed-effects regression modelling of lung function was performed, with co-variate parameters evaluated by likelihood ratio comparison. RESULTS: We included 271 ART-naïve and 197 ART-established children (median age 11 years in both groups) incorporating 1144 spirometric assessments. Changes in FEV(1) and FVC were associated with age at ART initiation and body mass index for both cohorts. Our models estimate that ART initiation earlier in life could prevent a deterioration of 0.04 FVCz/year. In the ART-naïve cohort, likelihood ratio comparison suggested an improvement in 0.09 FVCz/year during the two years following treatment initiation, but no evidence for this among participants established on ART. CONCLUSION: Early ART initiation and improved nutrition are positively associated with lung function and are important modifiable factors. An initial improvement in lung growth was seen in the first 2-years following ART initiation, although this did not appear to be sustained beyond this timeframe.